Prevalence and Pattern of Complications Associated with Type 2 Diabetes Mellitus among Patients Presenting to a Tertiary Hospital in Zambia - Nyirenda, Christopher; Namfukwe, Taonga; Maliko, Catherine; Chinkoyo, Sebastian; Zulu, Mabvuto; Maksoud, Gamal; Chimese, Mwinsa (British Journal of Healthcare and Medical Research, 2023)
Objective: To establish the prevalence and type of complications associated with type 2 diabetes mellitus among patients reporting for care at the Ndola Teaching Hospital. Design and Methods: The study team conducted a medical records based retrospective study which primarily assessed clinicians’ compliance to the recommended standards of management of diabetic patients. Further, the study examined the records for the presence and type of complications reported among the type 2 diabetic patients presenting for care. The study was undertaken at Ndola Teaching Hospital, a tertiary referral hospital in the Copper belt province of Zambia. The target population were adult male and female patients with type 2 diabetes. The period under review was from January 2022 to December 2022. The sample size estimate was determined using the Cochrane formula and a systematic random sampling procedure was applied to select the population of interest. A data abstraction sheet was used to collect the relevant medical information suggesting baseline characteristics and DMT2 associated complications. The type of complications were recorded based on the clinical and laboratory examination findings. The data was analyzed using excel and SPSS version 26. Results: Up to 90 eligible patient files representing the study subjects, 65.6% were female and 34.4% were males. The age range of the sampled population was from 20 to 80 years with most of the patients falling between 50-64 years representing about 34% and the least age category of above 80 years representing 2.25% of the study subjects. The mean age was 54 years. A number of files were devoid of a targeted comprehensive physical examination assessments. For example, out of 90 patients sampled, (n=12, 13.3%) had comprehensive foot examination and only 28.9% had their eyes fully examined. The most common complications associated with DMT2 were retinopathy (n=19, 21.1%), nephropathy (n=15, 16.7%), neuropathy (n=12, 13.3%) and coronary artery disease (n=10, 11.1%). Conclusion: Neurovascular complications are relatively common among the type 2 diabetes mellitus patients presenting for care at Ndola Teaching Hospital and do signify the need to optimize the standard of care administered.